2005
DOI: 10.1111/j.1443-9573.2005.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome and inflammatory bowel disease: interrelated diseases?

Abstract: In the past inflammatory bowel disease (IBD), celiac disease and irritable bowel syndrome (IBS) were regarded as completely separate disorders. Now, with the description of inflammation, albeit low-grade, in IBS, and of symptom overlap between IBS and celiac disease, this contention has come under question. Is there true overlap between these disorders? Despite the limitations of available data one cannot but be struck by some areas of apparent convergence: IBD and celiac disease in remission, lymphocytic coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 112 publications
2
39
1
Order By: Relevance
“…IBS has a heterogeneous clinical presentation that includes abnormal bowel movements and abdominal pain, which are also symptoms of inflammatory bowel disease (IBD) (8)(9)(10). In addition, Schoepfer et al reported that antibodies against flagellin, the primary structural component of bacterial flagellae, were significantly more frequent in IBS patients than in control patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…IBS has a heterogeneous clinical presentation that includes abnormal bowel movements and abdominal pain, which are also symptoms of inflammatory bowel disease (IBD) (8)(9)(10). In addition, Schoepfer et al reported that antibodies against flagellin, the primary structural component of bacterial flagellae, were significantly more frequent in IBS patients than in control patients (7).…”
Section: Introductionmentioning
confidence: 99%
“…Here, still the debate continues regarding potential overlap between IBS, IBD and celiac sprue [2] . Do reported instances of celiac sprue among patients with "typical" IBS, or the occurrence of IBS-type symptoms among IBD patients in apparent remission, reflect a true association between these disorders and, thereby, the effects of low grade inflammation on enteric nerve and muscle function, or does such apparent overlap simply serve to emphasize the non-specificity of many gastrointestinal symptoms?…”
Section: Diagnosismentioning
confidence: 99%
“…A history of a gastrointestinal infectious episode is also associated with the development of IBS in 18% of these patients (9). IBS can also appear in patients with inflammatory bowel disease (IBD) who are in remission (10). A unifying hypothesis for the generation of symptoms of IBS incorporates a central component (psychological factors), together with peripheral organ dysfunction (motility disorders, visceral hypersensitivity), possibly aggravated by microscopic inflammation and/or previous intestinal infection.…”
Section: Introductionmentioning
confidence: 99%